Effect of occurrence modes of nickel and vanadium on gasification characteristics of petroleum coke. (1st March 2020) - Li, Tianyu; Wang, Ben; Li, Wei; Nie, Jun; Song, Zijian; Yang, Wu; Ma, Chuan; Sun, Lushi
Highlights: Petcoke with various occurrence modes is derived by sequential chemical extraction. The effects of occurrence modes on reactivity and gas products are evaluated. Carbonates are unfavorable for gasification and can be selectively removed. Exchangeable form promotes aromatic ring decomposition to increase gas quality. Marine petcoke forms more disordered structures than continental facies. Abstract: This study investigates the effect of the occurrence modes of nickel (Ni) and vanadium (V) on char structure and reactivity during the steam gasification of petroleum coke (petcoke) in a fixed-bed reactor. Sequential extraction is applied to obtain the occurrence modes of Ni and V. Results indicates that Ni and V associated with the exchangeable form strongly promotes gasification reactivity and increases the methane yield by accelerating aromatic structure decomposition. The carbonates restrain pore structure development by increasing the graphitization degree to lower reactivity and gas yields. The exchangeable form and Fe-Mn oxides are beneficial to the micropore structure development. In comparison with continental petcoke, marine facies form highly disordered structures because high Ni and V contents can promote the pore structure formation. The carbonates strongly lower the reactivity of char and are unfavorable for the heat value of syngas, which should be selectively removed before gasification.